Development of a Blockchain-Based Food Safety System for Shared Kitchens - Hyejin Jang; Daye Lee; Byungun Yoon (Systems)
With the recent growth of the sharing economy, businesses offering shared-kitchen services are expanding rapidly. Due to the communal nature of these kitchens, there is a heightened need for systematic food safety management. However, existing research on blockchain applications has largely overlooked shared kitchens, a complex setting with numerous stakeholders and sensitivity to real-time kitchen conditions. This study addresses this gap by proposing a blockchain-based food safety management system for shared kitchens. The system’s functional requirements were meticulously outlined based on guidelines from South Korea’s Ministry of Food and Drug Safety. Key participants were identified as system users, and use cases were crafted in alignment with their responsibilities and roles to ensure effective safety management. Additionally, the blockchain system’s mechanisms for enhancing safety in shared kitchens were substantiated through specific use cases and detailed data structures, addressing issues related to forgery, alteration, and management challenges. This study also offers practical insights that can facilitate more structured safety management in shared-kitchen environments.